Oligoribonuclease is a central feature of cyclic diguanylate signaling in Pseudomonas aeruginosa - Cohen, Dorit (Proc Natl Acad Sci U S A, 2015)
The second messenger cyclic diguanylate (c-di-GMP) controls diverse cellular processes among bacteria. Diguanylate cyclases synthesize c-di-GMP, whereas it is degraded by c-di-GMP–specific phosphodiesterases (PDEs). Nearly 80% of these PDEs are predicted to depend on the catalytic function of glutamate-alanine-leucine (EAL) domains, which hydrolyze a single phosphodiester group in c-di-GMP to produce 5ʹ-phosphoguanylyl-(3ʹ,5ʹ)-guanosine (pGpG). However, to degrade pGpG and prevent its accumulation, bacterial cells require an additional nuclease, the identity of which remains unknown. Here we identify oligoribonuclease (Orn)—a 3ʹ→5ʹ exonuclease highly conserved among Actinobacteria, Beta-, Delta- and Gammaproteobacteria—as the primary enzyme responsible for pGpG degradation in Pseudomonas aeruginosa cells. We found that a P. aeruginosa Δorn mutant had high intracellular c-di-GMP levels, causing this strain to overexpress extracellular polymers and overproduce biofilm. Although recombinant Orn degraded small RNAs in vitro, this enzyme had a proclivity for degrading RNA oligomers comprised of two to five nucleotides (nanoRNAs), including pGpG. Corresponding with this activity, Δorn cells possessed highly elevated pGpG levels. We found that pGpG reduced the rate of c-di-GMP degradation in cell lysates and inhibited the activity of EAL-dependent PDEs (PA2133, PvrR, and purified recombinant RocR) from P. aeruginosa. This pGpG-dependent inhibition was alleviated by the addition of Orn. These data suggest that elevated levels of pGpG exert product inhibition on EAL-dependent PDEs, thereby increasing intracellular c-di-GMP in Δorn cells. Thus, we propose that Orn provides homeostatic control of intracellular pGpG under native physiological conditions and that this activity is fundamental to c-di-GMP signal transduction.